'Sexual misery' or 'happy British Muslims'?: Contemporary depictions of Muslim sexuality. (February 2019) - Chambers, Claire; Phillips, Richard; Ali, Nafhesa; Hopkins, Peter; Pande, Raksha
We begin this article with a close look at some contemporary pictures of sexual life in the Muslim world that have been painted in certain sections of the Western media, asking how and why these pictures matter. Across a range of mainstream print media from the New York Times to the Daily Mail, and across reported events from several countries, can be found pictures of 'sexual misery'. These 'frame' Muslim men as tyrannical, Muslim women as downtrodden or exploited, and the wider world of Islam as culpable. Crucially, this is not the whole story. We then consider how these negative representations are being challenged and how they can be challenged further. In doing so, we will not simply set pictures of sexual misery against their binary opposites, namely pictures abounding in the promise of sexual happiness. Instead, we search for a more complex picture, one that unsettles stereotypes about the sexual lives of Muslims without simply idealising its subjects. This takes us to the journalism, life writing and creative non-fiction of Shelina Zahra Janmohamed and the fiction of Ayisha Malik and Amjeed Kabil. We read this long-form work critically, attending to manifest advances in depictions of the relationships of Muslim-identified individuals over the last decade or so, while also remaining alert to lacunae and limitations in the individual representations. More broadly, we hope to signal our intention to avoid both Islamophobia and Islamophilia in scrutinising literary texts.